Effectiveness of the Bridges Learning Program in Enhancing Educational Elements from the Perspective of Teachers in the Northern Mazar Governorate - Al-Khateeb, Fatima Saleh Ali (Journal of Educational and Psychological Sciences, 2024)
This study aimed to investigate the effectiveness of the Bridges Learning Program in enhancing educational elements from the perspective of teachers in the Northern Mazar Governorate who teach the four core subjects. The study population consisted of 454 teachers, while the sample size was 85 teachers. The researcher used a descriptive-analytical method to collect data and gather opinions from teachers about the program and its effectiveness. The researcher used the Likert scale to gauge opinions and built a questionnaire consisting of 32 items. The questionnaire was reviewed by a panel of experts to ensure its validity and reliability. The study results showed a moderate level of effectiveness across all five fields, indicating that the Bridges Learning Program activities had a positive impact on students' acquisition of educational experiences, teachers' performance in educational practices, enriching curriculum content, improving educational management, and providing material resources for implementing Bridges Learning Program activities from the teachers' perspective.
Keywords: Bridges Learning Program Activities; Educational Elements